PEMBERANGUSAN SERIKAT PEKERJA DI DAERAH ISTIMEWA YOGYAKARTA - Hernawan, Ari; Pramuwardhani dewi, Murti (Yustisia, 2013)
AbstractThis research aims to determine the forms of suppression of union in Yogyakarta Special region and the efforts made by the trade unions of workers in Yogyakarta Special region in the face of acts of suppression of trade unions. This research is normative and empirical. data obtained through library research and field research. Data obtained in the study were analyzed qualitatively. Analytical results presented descriptively. result showed suppression of forms of union trade in the Special region of Yogyakarta form unions impede the establishment, transfer, suspension, and termination of employment for trade union who are performing their roles and functions, criminalization and the establishment of a rival unions. Efforts made trade union-trade union in Yogyakarta Special region in the face of acts of suppression of trade unions is to provide guidance in legal proceedings and internal awareness to its members. Just that more efforts to overcome due to the form of suppression of unions and not the cause suppression of trade unions.Key words : Suppression, Trade Unions, WorkerAbstrakPenelitian ini bertujuan untuk mengetahui bentuk-bentuk pemberangusan serikat pekerja di Daaerah Istimewa Yogyakarta dan upaya yang dilakukan serikat pekerja-serikat pekerja di Daerah Istimewa Yogyakarta untuk menghadapi tindak pemberangusan serikat pekerja. Penelitian bersifat yuridis normatf dan empiris melalui penelitian kepustakaan dan lapangan. Data dianalisis secara kualitatif. Hasil analisis disajikan secara deskriptif. Hasil penelitian menunjukkan bentuk-bentuk pemberangusan serikat pekerja berupa menghalangi pembentukan serikat pekerja, mutasi, skorsing, PHK dan kriminalisasi pengurus serikat pekerja serta pembentukan serikat pekerja tandingan. Upaya yang dilakukan serikat pekerja-serikat pekerja di Daerah Istimewa Yogyaakarta dalam menghadapi tindak pemberangusan dengan mendampingi anggota dan sesama pengurus dalam proses hukum dan penyadaran internal anggotanya. Upaya lebih ditujukan pada mengatasi akibat pemberangusan dan bukan faktor penyebabnya.Kata kunci : Pemberangusan, Serikat Pekerja, Pekerja